'I mean what is depression?' A qualitative exploration of UK general practitioners' perceptions of distinctions between emotional distress and depressive disorder. Issue 12 (15th December 2019) - Geraghty, Adam W A; Santer, Miriam; Beavis, Charlotte; Williams, Samantha J; Kendrick, Tony; Terluin, Berend; Little, Paul; Moore, Michael
Abstract : Objective: Detection of depression is a key part of primary mental healthcare. However, determining whether depressive disorder is or is not present in primary care patients is complex. The aim of this qualitative study was to explore general practitioners' (GPs) perceptions of distinctions between emotional distress and depressive disorder. Design: Qualitative interview study. Setting: Face-to-face and telephone interviews with GPs from the South of England. Participants: GPs working in UK primary care practices (n=21). Method: Interviews followed a semi-structured interview guide, were audio recorded and transcribed. Data were analysed thematically. Results: Views were divergent when directly considering whether emotional distress could be distinguished from depressive disorder. Some GPs suggested a distinction was not possible as symptoms lay on a continuum, with severity as a proxy for disorder. Others focused on the difficulty of the distinction and were uncertain. Some GPs perceived a distinction and referred to emotional distress as more likely in the presence of a stressor with the absence of biological symptoms. It was also common for GPs to refer to endogenous and reactive depression when considering possible distinctions between distress and depressive disorder. Conclusions: GPs' perceptions of when emotional symptoms reflect disorder varied greatly, with a broad range of views presented. Further research is needed to develop more consistent frameworks for understanding emotional symptoms in primary care.